A systematic review of the Australian food retail environment: Characteristics, variation by geographic area, socioeconomic position and associations with diet and obesity. (4th December 2019) - Needham, Cindy; Sacks, Gary; Orellana, Liliana; Robinson, Ella; Allender, Steven; Strugnell, Claudia
Summary: There is strong support across multiple sectors for the implementation of policies to create healthier food environments as part of comprehensive strategies to address obesity and improve population diets. The existing evidence base describing food retail environments and their relationship with health outcomes is limited in several respects. This systematic review examines the current evidence regarding food retail environments in Australia, including associations with diet and people with obesity, and socioeconomic and geographic disparities. Three databases were searched and independently screened. Studies were included if they were undertaken in Australia and objectively measured the food retail environment. Sixty papers were included. The broad range of methodological approaches used across studies limited the ability to synthesize the evidence and draw conclusions. Results indicated that there is some evidence that disparities exist in food retail environments across measures of socioeconomic position and geographic area in parts of Australia. Overall, there were inconsistent findings regarding the association between the healthiness of food retail environments and diet or people with obesity. Findings support previous calls for standardized tools and measures for monitoring the healthiness of food retail environments. This is imperative to inform evidence‐based policy and evaluation in this critical component of recommended obesity prevention strategies.